Technologies for solar thermal energy : theory, design and optimization - Hasanuzzaman, Md. (Energy and sustainable development expert) (Academic Press, 2022)
Technologies for Solar Thermal Energy: Theory, Design and Optimization presents concepts surrounding industrial process heat and thermal power generation, including detailed theory and practical considerations for design, performance analysis, and economic assessments. Addressing the significance of power generation from solar thermal energy, the book covers the different power cycles for solar thermal power plant and comparison analysis, along with the advantages of solar thermal power systems compared with photovoltaic systems, corresponding energy storage technology, working materials, and the design method of a solar thermal power plant.